Leading Sustainable Digital Transformation: The Role of Digital Leadership in Digital and Green Economy - Ashalia, Fania; Rahadika; Widyawati, Nadya Maharani; Sahertian, Pieter (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: Sustainable digital transformation is increasingly becoming a strategic agenda for public and private organizations to increase competitiveness while achieving sustainability targets. This study aims to explore the role of digital leadership in guiding transformation that is innovative, responsible, and aligned with sustainability principles. Background Problems: The increasing global demand for a digital economy and a green economy requires organizations to integrate technology while considering social and environmental impacts. However, many organizations still focus on technology adoption without developing the adaptive and collaborative culture necessary for sustainable transformation. Furthermore, the suboptimal innovation ecosystem involving government, industry, and society is a barrier to maximizing the benefits of digital transformation for sustainable development. Research Methods: This study uses a conceptual analysis approach to examine how digital leaders guide sustainable transformation through strategic vision, talent management, technology utilization, and the integration of sustainability principles into the organization’s business model. Finding/Results: : The study shows that effective digital leadership emphasizes not only the adoption of technologies such as artificial intelligence, data analytics, and automation, but also building an organizational culture that is adaptive, collaborative, and sensitive to environmental impacts. Digital leaders play a crucial role in creating a cross-stakeholder innovation ecosystem that connects digital economy goals—efficiency, scalability, and technology-based added value—with green economy goals such as emissions reduction, energy efficiency, and a circular economy. Conclusion: This study emphasizes that digital transformation strategies must be designed comprehensively, considering environmental, social, and governance (ESG) dimensions. Digital leadership serves as a catalyst capable of navigating the complexities of technology and sustainability, and plays a role in guiding organizations toward a green, inclusive, and sustainable digital economy. This study provides both conceptual contributions and practical implications for organizations transitioning to sustainability-based business models.